The Effect of Bone Marrow Mesenchymal Stem Cells on Vitamin D3 Induced Monocytic Differentiation of U937 Cells - Molaeipour, Zahra (Adv Pharm Bull, 2016)
Purpose: Mesenchymal stem cells (MSCs) are key components of the hematopoietic stem cells (HSCs) niche. They control the process of hematopoiesis by secreting regulatory cytokines, growth factors and expression of important cell adhesion molecules for cell-tocell interactions. In this research, we have investigated the effect of bone marrow derived MSCs on monocytic differentiation of U937 cells line. Methods: U937 cells were cultured in both direct co-culture with MSCs and MSCs conditioned medium (C.M) driven. This study used 1,25-dihydroxyvitamin D3(VitD3) as inductor of monocytic differentiation and U937 cells treated with VitD3 morphology was examined by Wright Giemsa staining. CD14 monocytic differentiation marker was measured by flow cytometry and monocytic gene expression was assessed by real time polymerase chain reaction (RT PCR). Results: The results of flow cytometric analysis showed that CD14 expression of U937 increased. The higher effect of MSCs co-culture on CD14 expression in U937 cells was observed, compared to the conditioned medium. Among ten monocytic related genes which were screened that was observed increase in 5 genes in which CXCR4 and CSF2RA showed significant increase. Conclusion: The results obtained show that MSCs have supportive effect on the monocytic differentiation of U937 cells. However, a distinct mechanism of that remains unclear.